Pengaruh Iklan dan Word of Mouth Terhadap Keputusan Pembelian Sabun Cuci Piring Cair Sunlight - Susanti Susanti; Alvyani Febriyanti; Fitri Prisliani; Zahra Suci Romadani; Ina Ratnasari (Jurnal Ilmiah Wahana Pendidikan, 2023)
Research on the Effect of Advertising and Word of Mouth on Purchase Decisions for Sunlight Liquid Dishwashing Soap (Empirical Study of Housewives in Rengasdengklok District, Karawang City) aims to determine and analyze the effect of Word of Mouth and advertising on purchasing decisions for sunlight liquid soap products in Rengasdengklok. This study uses a quantitative approach. The results of the research and discussion show that the Word of Mouth (X2) and (X2) for Sunligh dish soap products are considered good by respondents, there is a correlation between Advertising (X1) and Word of Mouth (X2) with a correlation coefficient value of 0.607 and has a relationship level strong because the value is positive, there is a partial effect of Advertising (X1) and Word of Mouth (X2) on Purchase Decisions (Y), and Advertising (X1) and Word of Mouth (X2) have a simultaneous influence on Purchase Decisions (Y).